Explicit instruction, input flood or study abroad: Which helps Japanese learners of English acquire adjective ordering?. (March 2019) - Hirakawa, Makiko; Shibuya, Mayumi; Endo, Marie
This article explores what kind of second language (L2) input influences Japanese learners' acquisition of adjective ordering restrictions (AOR) in English where Japanese exhibits no AOR. In Study I, an explicit instruction (EI) group ( n = 13) and a natural exposure (NE) group ( n = 12) responded to a preference task. In Study II, an input flood (IF) group ( n = 15) and a NE group ( n = 16) were involved in the same task. The EI group received 90-minute EI across three weeks while the IF group received positive evidence with multiple adjectives over 15 weeks. The NE groups participated in three or five-week intensive study-abroad programs in North America. Results from the two studies showed that many of the participants failed to make correct choices at the pre-test indicating difficulty with AOR and that only the EI group improved in their performance at the post-tests. We claim that positive evidence alone does not guarantee L2 acquisition of AOR.